Greco-Roman Jewellery from the Necropolis of Qasrawet (Sinai) - Rosenthal-Heginbottom, Renate (Journal of Hellenistic Pottery and Material Culture, 2020)
The ancient site of Qasrawet is situated south-west of Qatieh, the largest oasis in northern Sinai, and 30 km. or one day’s journey east of Pelusium and 10 km. south of the el-‛Arish- Qantara road on one of the minor roads leading from northern Sinai to the Gulf of Suez, and is tentatively identified with Castrum Autaei. First occupied in the 2nd century BCE and abandoned, though not violently destroyed in the late 2nd or early 3rd century CE, Qasrawet served as transit for Nabatean caravans on their way to the Gulf of Suez. In the necropolis Clédat investigated six tombs and three mausolea; two burials (Tombs 1–2) were again cleaned in the later campaign under Oren and Netzer. Clédat noted three types of burials. First, the dead were placed in a shallow cavity of a metre or less into the ground, so that the body was hardly covered by the soil. Second, the dead were laid into a bottomless coffin constructed of stone or brick. The cover was formed by slabs of limestone, held together by plaster. Since the shape recalls Egyptian anthropoid sarcophagi Clédat speaks of the sarcophagus type. These two types had no tomb marker. The grave-goods comprised mainly jewellery. Third, there are chamber tombs built of ashlar and reached through a vaulted corridor with steps, the mausolea. Since all were pillaged in antiquity no items of personal adornment were found in situ; some clay vessels and a horned altar were recovered. When remains of the skeleton were retrieved the dead were found to have been placed on their back facing east.